The Fox or Mr Fox?: Particularization of the bare noun - Borah, Gautam K. (Journal of Modern Languages, 2014)
In numeral classifier languages a dog-type noun (i.e. a noun that refers to a kind subsuming some similar individuated entities or things) is also an NP by default. This in turn means that unlike in an English-like language, the move from the general (as is indicated by a noun) to the particular (as is indicated by an NP) is not grammatically marked in such a language. The current paper demonstrates how Assamese, a numeral classifier language spoken in Assam, a north eastern province of India, allows the bare noun to be used at the sentential level for different degrees of particularity. Thus, in the following example from Assamese (taken from a popular folk tale) tetiā xiāl-e kole…. [tetiā ‘then’; xiāle ‘fox-NOM’; kole ‘said’] the bare noun xiāl ‘fox’ is used as an NP, precisely as a proper name. The paper thus argues that we have a better English translation of the concerned Assamese sentence in “Mr Fox then said…” rather than in “The fox then said….”. The Assamese data used in the paper comes from the author’s native speaker competency in the language.